An Estimation of CPI Biases in Argentina 1985-2005, and its Implications on Real Income Growth and Income Distribution - Pablo Gluzmann; Federico Sturzenegger (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2009)
We use the shifts in Engel curves estimated from household surveys to estimate CPI biases in Argentina between 1985 and 2005. We find that real earning levels increased during this period between 4.3 and 5.7% faster per year than previously estimated. More surprisingly, relative to conventional wisdom, that income distribution has improved throughout this period.
Keywords: 330; Verbraucherpreisindex; Nachfragetheorie des Haushalts; Argentinien